Vaginal administration of isosorbide mononitrate for cervical ripening prior to induction of labor for postdated pregnancy: a randomized controlled trial - Rai, Rubina; Basnet, P; Thakur, A; Pradhan, T (Journal of BP Koirala Institute of Health Sciences, 2018)
Introduction: Induction of labor is commonly practiced intervention in modern Obstetrics. The aim of induction of labor is to initiate labor when maternal and fetal conditions necessitate delivery before the onset of spontaneous contraction with purpose to achieve safe vaginal delivery. Induction of labor is one of the most commonly practiced interventions in the Department of Obstetrics and Gynecology every day. The success of this obstetric practice is highly dependent upon the condition of the cervix which is assessed with Bishop‟s Score and it is well known that unfavorable cervix is associated with failure of induction and cesarean section. In the recent years, there has been a considerable interest in the use of nitrous oxide donors for cervical ripening and labor induction.Objective: To evaluate whether isosorbide mononitrate administered vaginally prior to induction in postdated pregnancy is effective for pre-induction cervical ripening and thus, improves the process of induction of labor.Methods: One hundred and twenty women scheduled for labor induction were recruited and assigned randomly to isosorbide mononitrate or placebo followed by misoprostol 25μg. The efficacy of the medication was evaluated by predetermined outcome variables for cervical ripening and induction of labor and delivery.Results: The groups were comparable with respect to age, gestational age and Bishop‟s score. Women receiving isosorbide with misoprostol didn‟t show any improvement in the Bishop‟s score compared to misoprostol and placebo. There was no significant difference between the two groups regarding time of delivery and onset of active stage of labor from induction. Cesarean delivery rates were similar between the two groups; however, the indications of the cesarean section were different between the two groups which were significant statistically. Neonatal outcome were similar between the two groups.Conclusion: The addition of vaginal isosorbide mononitrate to oral misoprostol for cervical ripening and labor induction did not reduce time to vaginal delivery and didn‟t help in improving pre-induction cervical score.Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, page: 51-58